Pengaruh Metode Pengajaran dan Motivasi Belajar terhadap Kemampuan Pemahaman Matematika Siswa - Sari, Ira Permata; Tarihoran, Andre Chadir (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2024)
This abstract discusses students' mathematical understanding abilities. The ability to understand mathematics is an important aspect of education that has a direct impact on student achievement. From this research, it can be concluded that factors such as teaching methods, learning motivation, and environmental support have a great influence on increasing students' understanding of mathematics. Interactive and contextual teaching methods are proven to be more effective than conventional methods. Apart from that, intrinsic and extrinsic motivation play an important role in encouraging students to be more active in the learning process. This study uses literature analysis methods to explore various examples of the application of Mathematical Understanding Skills for Students. The results show that a good understanding of mathematics can facilitate decision making and increase efficiency in various activities. In conclusion, a deep understanding of Mathematical Comprehension Ability has significant practical value in increasing the effectiveness of resource management and process optimization in various aspects of daily life.